LDL-C goal achievement and lipid-lowering therapy in patients by atherosclerotic cardiovascular disease subtype: the SANTORINI study. (3rd October 2022) - Catapano, A L; Manu, M C; Burden, A; Ray, K K
Abstract: Background: In the 2019 ESC/EAS guidelines, documented ASCVD is a criterion for patients being categorised as at very high cardiovascular (CV) risk, and stringent low-density lipoprotein cholesterol (LDL-C) reductions of ≥50% plus a goal of <1.4 mmol/L are recommended. Intensive lipid lowering therapy (LLT) is therefore key to reducing the risk of future CV events. Purpose: To describe patient characteristics, approaches to lipid management and LDL-C goal attainment at baseline in the subgroup of secondary prevention patients with a history of ASCVD enrolled in the SANTORINI study. Methods: SANTORINI is a multinational observational study (NCT-04271280) evaluating the real-world use of LLT in adult patients with high- and very-high CV risk enrolled from primary and secondary care sites across Europe between March 2020 and February 2021. The ASCVD status of patients was defined based on medical records as either coronary (myocardial infarction; unstable angina; angina pectoris; coronary artery bypass graft surgery; percutaneous transluminal coronary angioplasty; coronary artery disease [CAD]; CAD unequivocal on imaging), cerebral (stroke; transient ischaemic attack; cerebrovascular disease; cerebrovascular disease unequivocal on imaging; carotid artery disease), peripheral/other (peripheral arterial disease [PAD]; lower extremity artery disease; PAD unequivocal on imaging; retinal vascular disease; abdominal aortic aneurysm; renovascular disease) or polyvascular (≥1 ASCVD). Results: Of the 9044 patients included in the analysis 6954 (76.9%) had a history of ASCVD. Baseline demographics and patient characteristics by type of ASCVD are shown in Table 1. The majority of patients were male (76.9%) and mean (SD) age was 66.1 (10.4) years. Mean (SD) LDL-C level was 2.29 (1.13) mmol/L and a total of 20.7% of patients achieved CV risk-based LDL-C goals. Fewer patients with cerebral ASCVD attained LDL-C goals (15.0%). Despite being at very-high CV risk, 21.4% of all patients had no documented LLT (up to 28.5% for the cerebral ASCVD group). The majority of patients (49.2%) received statin monotherapy, particularly moderate (21.8%) and high-intensity statins (24.9%). The peripheral/other ASCVD and cerebral ASCVD groups recorded the highest use of monotherapy across subgroups (≥57.8%), whereas any other LLT alone was consistently low, including ezetimibe (≤2.5%) and PCSK9i (≤2.0%). Overall, only 25.6% of patients received combination therapy (17.5% statin + ezetimibe; 4.7% PCSK9i + statin and/or ezetimibe; 3.4% other). Conclusion: The SANTORINI baseline analysis shows that the majority of patients with ASCVD do not achieve their LDL-C goals. The underutilisation of combination therapy in this very high CV risk population highlights the need to move beyond high-intensity statin monotherapy and rather focus on combination therapies which achieve more intensive LDL-C reductions, thus improving LDL-C goal attainment. Funding Acknowledgement: Type of funding sources: Private company. Main funding source(s): Daiichi Sankyo Europe GmbH, Munich, Germany